POPULASI IMAGO Sitophilus oryzae L (Coleoptera: Curculionidae) PADA BEBERAPA JENIS BERAS ASAL DESA WAIMITAL KECAMATAN KAIRATU - Lia A Booroto; Nureny Goo; Saartje H Noya (Universitas Pattimura, 2017)
The objective of this study was to determine the population of Sitophilus oryzae imago on rice from 5 varieties of paddy from Waimital Village. The rice used in this research were taken directly from rice mill in Waimital Village. Completely Randomized Design with 5 treatments and 3 replications was used in this study. Two trials were used in this research. The first experiment was to investigate the incidence of imago S. oryzae each week, and the second trial to calculate the population on rice stored for 8 weeks. The results showed that there was a different period of development of S. oryzae every week on five types of rice. While for 8 weeks storage, the highest population of S. oryzae imago was on variety of Inpari 21 with 184.00 beetles, and the lowest was on variety of Cimelati with 64.67 beetles. The population on the other 3 varieties (Mekongga, Ciherang, and IR64) were 176.33, 133.33 and 76.33 respectively